Numerical Simulation of Low-Permeability Reservoirs with considering the Dynamic Boundary Layer Effect - Chuanzhi Cui; Yingfei Sui; Xiangzhi Cheng; Yinzhu Ye; Zhen Wang (Geofluids)
Surface active components, salt component, and polar molecules in the fluid may adsorb on the solid surface and form the boundary layer during low-speed flow in a porous medium, which will influence the flowing law in the porous medium. Previous studies on flowing in low-permeability reservoirs mainly focus on the effects of the threshold pressure gradient. But few of them have considered the time-varying effect of the boundary layer thickness in solving the numerical simulation. The correlation among the boundary layer thickness and pressure gradient was established by regressing the experimental data of boundary thickness versus pressure. On this basis, the mathematical model of oil-water two-phase flow which involves influence of the boundary layer was constructed, and the comparative analysis of the development effect is performed. Results demonstrated that the boundary layer thickness is sensitive to the throat radius and pressure gradient, and the boundary layer thickness decreases dynamically with the increase of pressure gradient. The displacement velocity and accumulative oil production with boundary layer effect decrease when comparing with that without the boundary layer effect. Meanwhile, the boundary layer accelerates the breakthrough of water. With the reduction of production pressure difference, the difference between accumulative oil production with and without the boundary layer effect increases, which indicate that the dynamic effect of the boundary layer is intensified.